Breast involvement in Wegener's granulomatosis - Pambakian, H. (1971)
Two cases of Wegener's granulomatosis are described in which the early and predominating lesions were found in the breast. The histological features of breast necrosis with granulomatous inflammation and widespread vasculitis in the breast in the absence of any demonstrable pathogens enabled a presumptive diagnosis to be made in one case before the development of the more characteristic clinical features in the respiratory system.